One year study on the reproductive biology, ovary characterization and age of the European sardine (Sardina pilchardus) in the middle-west Adriatic Sea - Chemello, Giulia; Cerrone, Greta Lucia; Tavolazzi, Valentina; Donato, Fortunata; Tiralongo, Francesco; Gioacchini, Giorgia (Frontiers in Marine Science, 2023)
The ecological and economic relevance of the European sardine (Sardina pilchardus) in the Adriatic area is well established. High exploitation rates and instability of environmental parameters could potentially impair the reproductive physiology of this species, compromising the stock’s stability. To guarantee efficient stock management, there is a need to fill the lack of updated information regarding the structure, sex ratio and reproductive season of the sardine population in the Adriatic Sea. The present study provides new data on the distribution of females’ maturation phases, sex ratio, age frequency and seasonality of the reproductive period in the middle-western Adriatic Sea. Sardine specimens were collected monthly, from April 2021 to March 2022 in the Adriatic waters off the coast of Ancona. Size, weight and sex were determined for a sub-sample of almost 144 specimens during each sampling period. Through otolith analysis and ovary characterization, population age and females’ maturation phase were estimated respectively. The results obtained highlighted a general reduction in size (15.5cm the highest size class) and age (maximum age 2+, greater than 2 years old but less than 3 years) of the population that was characterized by the predominance of males. Also, an interesting scarcity of small female specimens (< 13 cm length) was observed. The reproductive period seemed to occur between October and June as suggested by ovarian characterization, GSI (0.50, 0.30 and 0.62 respectively) and Fulton’s condition factor (0.73, 0.74 and 0.74 respectively) analysis that showed the lowest values in July, August and September corresponding to the rest period.